Law and Values in Governance: The Singapore Way - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2000)
The article examines the role of law and the legal system in catalysing Singapore's development success. It argues that there is a dichotomy in the approach with regard to commercial law and law relating to individual freedom and rights and civil society. Universalism characterises the treatment of commercial laws while cultural relativism and a communitarian-based understanding of rights and obligations are features of the law relating to the rights of the individual. Instrumentalism, driven by a particularistic 'communitarian' political philosophy underpinned by strong Confucianist values, is very much motivated by the need for good governance as a prerequisite for economic growth and to nourish the nascent nation-building process. This helps to explain the universalism-relativism dichotomy in the approach to different laws. While it is argued that there is a strong element of instrumentality in its treatment of the legal system and the law, the government has always been careful to ensure that the laws and the legal system enjoy widespread public support and legitimacy. Such a trend is also anticipated for the Hong Kong SAR, another ethnic Chinese-majority political entity, provided that political expediency and a neo-colonial attitude are not the motivating concerns of the Beijing government.